Peningkatan Pemahaman Masyarakat Terhadap Zakat (Studi Kasus Di Nagari Sungai Nanam, Kecamatan Lembah Gumanti Kabupaten Solok Provinsi Sumatera Barat) - Sindi Maida Dwi Yanti; Hafizzullah Hafizzullah; Emrizal Emrizal (Institute of Research and Community Service Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The main problem examined in this research is increasing the understanding of the people of Nagari Sungai Nanam regarding zakat and the steps that can be taken by the Nagari Sungai Nanam to increase the community's understanding of the distribution of zakat and the efforts made to increase the community's understanding of the distribution of zakat. This type of research is field research with qualitative descriptive methods. The results of field research show that the community in Nagari Sungai Nanam's understanding of zakat is quite high. The community's understanding is divided into three groups based on the results of interviews with 12 people interviewed from several communities. A total of 3 people do not understand zakat which is called understanding (translation), 4 people have a basic understanding of zakat which is called understanding (interpretation), and 5 people have understood zakat in depth which is called understanding (exploration). Regarding the distribution of zakat, it shows that the people of Nagari Sungai Nanam have their zakat distributed in two ways, namely, through amil zakat (BAZNAS) and given to mustahik directly.